2022
DOI: 10.18632/aging.203949
|View full text |Cite
|
Sign up to set email alerts
|

Manual therapy regulates oxidative stress in aging rat lumbar intervertebral discs through the SIRT1/FOXO1 pathway

Abstract: With the increasing burden of a globally aging population, low back pain has become one of the most common musculoskeletal disorders, caused mainly by intervertebral disc (IVD) degeneration. There are currently several clinical methods to alleviate back pain, but there is scarce attention paid as to whether they can improve agerelated IVD degeneration. It is therefore difficult to conduct an in-depth evaluation of these methods. A large number of clinical studies have shown that manual therapy (MT), a widely u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…In addition, activation of SIRT1 can ameliorate oxidative stress mediated p53-p21-Rb and p16-Rb related cellular senescence. [157][158][159] In addition to SIRT1, SIRT2 also inhibits oxidative stress-induced IVD cell injury. Yang et al 160 found that SIRT2 overexpression inhibited oxidative stress by upregulating the expression of SOD1/2 and suppressed NPCs senescence by downregulating p53-p21-Rb levels.…”
Section: Sirtmentioning
confidence: 99%
“…In addition, activation of SIRT1 can ameliorate oxidative stress mediated p53-p21-Rb and p16-Rb related cellular senescence. [157][158][159] In addition to SIRT1, SIRT2 also inhibits oxidative stress-induced IVD cell injury. Yang et al 160 found that SIRT2 overexpression inhibited oxidative stress by upregulating the expression of SOD1/2 and suppressed NPCs senescence by downregulating p53-p21-Rb levels.…”
Section: Sirtmentioning
confidence: 99%
“…In this situation, the quantification and standardization of MT are the challenges for current research. Recently, we have conducted research in the field of MT intervention in pain [25][26][27] and confirmed its exact efficacy and few possible mechanisms, but further research is needed. In this study, "Weizhong" (BL40) was selected as the implementation site of MT because of its specific efficacy in low back and leg pain according to previous studies [47][48][49] and because BL40 is located behind the knee joint, which can avoid affecting wound healing after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Half of the rats in the CCD group were randomly classified for MT intervention. Based on our previous studies [ 25 27 ], specific MT intervention was performed as follows: (1) the intervention started on the 4th day after surgery and was performed once a day for 10 min for 18 consecutive days; (2) rats were handled by the experimenters to adapt 30 min before the intervention; (3) the right thumb of the experimenter was used to press and knead the “Weizhong” (BL40) point on the right lower extremity of the rat, which is located in the center of the crease of the popliteal fossa [ 28 ] (Fig. 1 A); (4) the right thumb was equipped with a tactile measurement finger sleeve (FingerTPS, Pressure Profile System, CA, USA) to maintain a constant stimulation pressure of 5 N and frequency of 2 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Two previous basic studies on animal experiments showed that pain behavior of mice was improved after simulating massage manipulation, which was associated with reduced peripheral inflammation mediated by the mechanosensitive channel protein Piezo and senescence-related pathways. 14,15 A recent study simulated the treatment process of tuina manipulation and found that the analgesic effect on a neuropathic pain model may be related to the inflammatory pathway regulated by noncoding RNA. 16 Yijinjing is a type of traditional Chinese exercise that puts emphasis on the coordination of posture, meditation, and breathing.…”
Section: Introductionmentioning
confidence: 99%
“…However, research on the direct physiologic mechanisms of tuina therapy for neck pain is relatively limited. Two previous basic studies on animal experiments showed that pain behavior of mice was improved after simulating massage manipulation, which was associated with reduced peripheral inflammation mediated by the mechanosensitive channel protein Piezo and senescence-related pathways . A recent study simulated the treatment process of tuina manipulation and found that the analgesic effect on a neuropathic pain model may be related to the inflammatory pathway regulated by noncoding RNA .…”
Section: Introductionmentioning
confidence: 99%